The Effect of Workplace Health and Safety on Eleventh Grade Student Learning Outcomes in the Lathe Machining Engineering Subject at State Vocational School 1 Lembah Melintang - Muhammad Azis Fuadi; Fiki Efendi; Eko Indrawan; Rizky Ema Wulansari (Jurnal Vokasi Mekanika (VoMek), 2025)
The adoption of occupational safety and health (OHS) in vocational education environments, especially Vocational High Schools (SMK), is a crucial element in supporting a safe and effective practical learning process. However, observations at SMKN 1 Lembah Melintang showed that the implementation of OHS principles was not optimal, including the absence of consistency in utilizing personal protective equipment (PPE) and the unavailability of structured practice SOPs. Based on these conditions, this research endeavors to explore the effect of implementing OHS measures on students’ educational outcomess in the Lathe Machining Engineering subject for grade 11. the research applies a quantitative methodology with an associative analysis technique. The study population was all 31 students of grade 11 Machining Engineering, who were also sampled through total sampling techniques. Data acquisition was performed via questionnaires and documentation, then analyzed employing validity, reliability, normality, linearity, simple linear regression, and t-test analyses with SPSS. The outcome of the study showed that a significant positive correlation between the implementation of OHS and student learning outcome. The computed correlation coefficient indicated 0.708 and the determination value (R²) of 0.501 indicate that K3 contributes 50.1% to the variation of learning outcomes. The t-test shows a t-value of 5.395 > t-table 1.699 which strengthens the significance of the influence. Thus, it can be concluded that K3 has a key element in supporting improvements in student performance in learning the practice of lathe machining techniques